Perancangan Sistem Pendukung Keputusan Penentuan Ketua Osis Dengan Menerapkan Metode Composite Performance Index (Cpi) (Studi Kasus : Smp Swasta Kavri Talun Kenas) - Suci Ananda Tarigan (Cattleya Darmaya Fortuna, 2021)
Decision support system is part of a computer-based information system that can be used to support decision making in an organization or company. Decision support systems can be generated using several methods, one of which is the Composite Performance Index (CPI) method. Composite Performance Index is a composite Index that can be used to determine the determination or ranking of various alternatives based on several criteria. Intra-School Student Organizations (OSIS) have a special function in preparing students to implement management systems and leadership.In determining the student council chairman has criteria, such as intelligence, behavior,craftsmanship, and neatness, which usually the school still records manually so that it is considered less effective.